(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The structure and stages of a lesson plan hold paramount importance in ensuring effective teaching and learning outcomes in any educational setting. A meticulously organized lesson plan guides both instructors and learners through the instructional process, offering clarity, coherence, and a purposeful direction for each session. The core components of a comprehensive lesson plan include its aims, procedures, and assessment strategies, which collectively contribute to the creation of a structured and dynamic learning environment.